Maintenance of Sustained Low Disease Activity or Remission in Patients With Rheumatoid Arthritis Treated With Etanercept Monotherapy: Results from the Corrona Registry. Issue 10 (29th September 2020) - Pappas, Dimitrios A.; Shan, Ying; Lesperance, Tamara; Kricorian, Greg; Karis, Elaine; Rebello, Sabrina; Hua, Winnie; Accortt, Neil A.; Stryker, Scott
Abstract : Objective: The purpose of this study was to evaluate maintenance of remission/low disease activity (LDA) in patients with rheumatoid arthritis (RA) who achieved remission/LDA with etanercept (ETN) plus a conventional synthetic disease‐modifying antirheumatic drug (csDMARD) and to compare patients who discontinued csDMARD to receive ETN monotherapy (Mono) with those remaining on combination therapy (Combo). Methods: Patients from the Corrona RA registry between October 1, 2001, and August 31, 2017, were eligible. The index date for the Mono cohort was the csDMARD discontinuation date; the index visit for the Combo cohort was estimated from time between ETN initiation and csDMARD discontinuation in the Mono cohort. The main outcome calculated was maintenance of remission/LDA. Patients were censored if they switched to or added a biologic DMARD, discontinued ETN, when a csDMARD was reintroduced (Mono), or if methotrexate increased more than 5 mg/d (Combo). Trimming was used to balance demographic and clinical characteristics between groups. Cox regression models were adjusted for the remaining differences across groups. Results: We identified 182 Mono and 403 Combo patients; 120 Mono and 207 Combo patients remained after trimming. Most patients (approximately 80%) were biologic medication–naive before initiating ETN. At 24 months postindex, modeled percentages of patients remaining in remission/LDA were 75% for Mono and 86% for Combo (overall adjusted P = 0.057). More patients were censored for therapy change in Mono than in Combo groups (37% versus 5%), largely due to reintroduction of csDMARDs in the Mono group. Conclusion: Many patients with RA who achieved remission/LDA on combination therapy maintained remission/LDA with ETN monotherapy for 2 years after csDMARD discontinuation. ETN monotherapy may be a viable option for patients who discontinue csDMARDs after achieving LDA/remission.